Minat Masyarakat Kota Banda Aceh terhadap Kartu Kredit Bank - Ismail Ismail (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2018)
The purpose of this study was to find out how the interest of the people of Banda Aceh City on credit cards, to find out the factors that influence the interest of the Banda Aceh City Community towards the Bank's credit card. The research was carried out in the city of Banda Aceh which included the customers of the Bank's credit card in the City of Banda Aceh. That is the Bank Customer as follows; (1). Bank BRI, (2). BNI Bank, (3). Bank Mandiri, (4). Maybank, (5). Bank BCA, (6). Bank Danamon, (7). Bank Bukopin, (8). Bank Permata, (9). Panin Bank. With the number of respondents as many as 270 respondents. Based on the KMO and Bartlett's test the values obtained were approx. Chi-Square is 717,400 at df = 21 with a probability level of 0,000 so that all the variables used as indicators for this study are used as references by the people of Banda Aceh to have a Bank credit card. The most dominant factors that cause public interest in credit cards in the sequence are cultural dimensions, social dimensions, personal dimensions, psychological dimensions, achievement dimensions, power dimensions, and affiliation dimensions.